2015
DOI: 10.3390/nu7095374
|View full text |Cite
|
Sign up to set email alerts
|

Phytosterols, Phytostanols, and Lipoprotein Metabolism

Abstract: The efficacy of phytosterols and phytostanols added to foods and food supplements to obtain significant non-pharmacologic serum and low density lipoprotein (LDL) cholesterol reduction is well documented. Irrespective of age, gender, ethnic background, body weight, background diet, or the cause of hypercholesterolemia and, even added to statin treatment, phytosterols and phytostanols at 2 g/day significantly lower LDL cholesterol concentration by 8%–10%. They do not affect the concentrations of high density lip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
83
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 122 publications
(90 citation statements)
references
References 45 publications
3
83
0
4
Order By: Relevance
“…Phytosterols are reported to reduce LDL-C, [34] which is consistent with our findings (Figure 4), and a previous study reported that ERG can relieve kidney injury in a streptozotocin-induced mouse model of DM. [15] Interestingly, we found that ERG can also protect the pancreas and liver in KK-A y diabetic mice ( Figures 6 and 7).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Phytosterols are reported to reduce LDL-C, [34] which is consistent with our findings (Figure 4), and a previous study reported that ERG can relieve kidney injury in a streptozotocin-induced mouse model of DM. [15] Interestingly, we found that ERG can also protect the pancreas and liver in KK-A y diabetic mice ( Figures 6 and 7).…”
Section: Discussionsupporting
confidence: 92%
“…The difference between phytosterols and cholesterols lies in the different side chain structure. It is reported that phytosterols have been added to food to reduce LDL-C. [34] As a member of the phytosterol group, ERG has many biological activities. A previous study reported that ERG can relieve kidney injury in a streptozotocininduced diabetic mice.…”
Section: Discussionmentioning
confidence: 99%
“…High intakes of phytosterols will lower cholesterol absorption and LDL concentrations in blood [18]. In the intestine, these phytosterols will eject cholesterol from mixed micelles, which can decrease cholesterol absorption resulting in low levels of cholesterol in the blood [19]. Hence the body synthesizes cholesterol to meet its needs [19].…”
Section: Biological Activities Of Phytosterolsmentioning
confidence: 99%
“…In the intestine, these phytosterols will eject cholesterol from mixed micelles, which can decrease cholesterol absorption resulting in low levels of cholesterol in the blood [19]. Hence the body synthesizes cholesterol to meet its needs [19]. There are other biological activities, but scientists do not know their significance to humans so far.…”
Section: Biological Activities Of Phytosterolsmentioning
confidence: 99%
See 1 more Smart Citation